2012
DOI: 10.1016/j.braindev.2011.10.004
|View full text |Cite
|
Sign up to set email alerts
|

A perfusion-metabolic mismatch in Sturge-Weber syndrome: A multimodality imaging study

Abstract: OBJECTIVE We combined perfusion weighted imaging (PWI) with 2-deoxy-2[18F]fluoro-D-glucose (FDG) positron emission tomography (PET) to study the relationship between regional metabolic and perfusion abnormalities and their clinical correlates in children with Sturge-Weber syndrome (SWS). METHODS Fifteen children (age: 0.9-10 years) with unilateral SWS underwent high-resolution PWI and FDG PET prospectively. Regional (lobar) asymmetry indices (AIs) of subcortical white matter (WM) cerebral blood flow (CBF) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…A recent study has demonstrated a general correlation between cerebral perfusion and metabolism; however, increased white matter perfusion with preserved cortical metabolism and overlying cortex was a common pattern of perfusion/metabolic mismatch [34]. This mismatch was theorized to represent a disease stage where cortical function is preserved while increased white matter perfusion provides collateral drainage of the cortex via the deep vein system.…”
Section: Sturge-weber Syndromementioning
confidence: 98%
“…A recent study has demonstrated a general correlation between cerebral perfusion and metabolism; however, increased white matter perfusion with preserved cortical metabolism and overlying cortex was a common pattern of perfusion/metabolic mismatch [34]. This mismatch was theorized to represent a disease stage where cortical function is preserved while increased white matter perfusion provides collateral drainage of the cortex via the deep vein system.…”
Section: Sturge-weber Syndromementioning
confidence: 98%
“…Relative findings leading to surgical decision are progressive atrophy and transient increase of glucose metabolism in the affected cerebral cortex on fluorodeoxyglucose–positron emission tomography (FDG‐PET) study. Transient hypermetabolism within the affected area in SWS is known as a finding in recent seizures . Therefore, we accept the transient hypermetabolism on FDG‐PET study as a relative indication for epilepsy surgery.…”
Section: Discussionmentioning
confidence: 97%
“…One would also anticipate a greater MCA and PCA (compared to ACA) relative decrease in mean flow velocity in the affected hemisphere, compared to the unaffected hemisphere, since SWS brain involvement is more commonly in posterior occipital, parietal, and temporal regions of the brain [18], as was seen in our cohort of subjects. The frontal lobe, perfused in part by the ACA, is the least likely region to be affected by SWS brain involvement [19].…”
Section: Discussionmentioning
confidence: 99%